Thymosin β 10 is overexpressed and associated with unfavorable prognosis in hepatocellular carcinoma - Song, Chunrong (Biosci Rep, 2019)
Thymosin β 10 (TMSB10) has been demonstrated to be overexpressed and function as an oncogene in most types of human cancer including hepatocellular carcinoma (HCC). In our study, we present more evidence about the clinical significance and biological function of TMSB10 in HCC. First, we observed levels of TMSB10 expression were obviously increased in HCC tissues compared with normal liver tissues at The Cancer Genome Atlas (TCGA) datasets. Furthermore, we confirmed that TMSB10 mRNA and protein levels were also increased in HCC tissue samples compared with normal adjacent normal liver tissue samples. In addition, we found high TMSB10 expression was remarkably associated with the advanced tumor stage, large tumor size, distant metastasis, and poor prognosis, and acted as an independent factor for predicting poor overall survival in HCC patients. Loss-of-function studies suggested silencing of TMSB10 expression dramatically reduced cell proliferation, migration, and invasion in HCC. In conclusion, TMSB10 may hold promise as a tumor biomarker for predicting prognosis and a potential target for developing a novel therapeutic strategy.